Clustering Patterns of Comorbidities Associated with In-Hospital Death in Hospitalizations of US Adults with Venous Thromboembolism - Tsai, James (Ivyspring International Publisher, 2013)
Background: Venous thromboembolism (VTE) is a significant source of mortality, morbidity, disability, and impaired health-related quality of life in the world. Objective: We aimed to evaluate the clustering patterns and associations of 29 comorbidities with in-hospital death among adult hospitalizations with a diagnosis of VTE in the United States by analyzing data from the 2009 Nationwide Inpatient Sample. Methods: This cross-sectional study included 153,124 adult hospitalizations with a diagnosis of VTE. Adjusted rate ratios and 95% confidence intervals (CI) for in-hospital death were generated by using multivariable log-linear regression models to measure independent associations between comorbidities and in-hospital death. Results: We estimated that 44,200 in-hospital deaths occurred in 2009 among 773,273 US adult hospitalizations with a diagnosis of VTE. Subgroups of hospitalizations with comorbidities of “congestive heart failure,” “chronic pulmonary disease,” “coagulopathy,” “liver disease,” “lymphoma,” “fluid and electrolyte disorders,” “metastatic cancer,” “peripheral vascular disorders,” “pulmonary circulation disorders,” “renal failure,” “solid tumor without metastasis,” or “weight loss” were positively and independently associated with 1.07 (95% CI: 1.02-1.12 ) to 2.06 (95% CI: 1.97-2.16) times increased likelihoods of in-hospital death, when compared to those without the corresponding comorbidities. The clustering patterns of these comorbidities by 4 disease categories (i.e., “cancer,” “cardiovascular/respiratory/blood,” “gastrointestinal/urologic,” and “nutritional/bodyweight”) were associated with 2.74 to 10.28 times increased likelihoods of in-hospital death, as compared to hospitalizations without any of these comorbidities. The overall increase in the cumulative number of comorbidities corresponded to significantly elevated risks (P-trend<0.01) for in-hospital death among hospitalizations with a diagnosis of VTE. Conclusion: The presence of multiple comorbidities is ubiquitous among hospitalizations of adults with VTE and among in-hospital deaths with VTE in the United States. The findings of our study further suggest that, among hospitalizations of adults with VTE, the presence of certain comorbidities or clustering of these comorbidities significantly elevates the risk of in-hospital death.